SP140–RESIST pathway regulates interferon mRNA stability and antiviral immunity - Kristen C. Witt; Adam Dziulko; Joohyun An; Filip Pekovic; Arthur Xiuyuan Cheng; Grace Y. Liu; Ophelia Vosshall Lee; David J. Turner; Azra Lari; Moritz M. Gaidt; Roberto Chavez; Stefan A. Fattinger; et al. (Nature, 2025)
Abstract Type I interferons are essential for antiviral immunity 1 but must be tightly regulated 2 . The conserved transcriptional repressor SP140 inhibits interferon-β ( Ifnb1 ) expression through an unknown mechanism 3,4 . Here we report that SP140 does not directly repress Ifnb1 transcription. Instead, SP140 negatively regulates Ifnb1 mRNA stability by directly repressing the expression of a previously uncharacterized regulator that we call RESIST (regulated stimulator of interferon via stabilization of transcript; previously annotated as annexin 2 receptor). RESIST promotes Ifnb1 mRNA stability by counteracting Ifnb1 mRNA destabilization mediated by the tristetraprolin (TTP) family of RNA-binding proteins and the CCR4–NOT deadenylase complex. SP140 localizes within punctate structures called nuclear bodies that have important roles in silencing DNA-virus gene expression in the nucleus 3 . Consistent with this observation, we find that SP140 inhibits replication of the gammaherpesvirus MHV68. The antiviral activity of SP140 is independent of its ability to regulate Ifnb1 . Our results establish dual antiviral and interferon regulatory functions for SP140. We propose that SP140 and RESIST participate in antiviral effector-triggered immunity 5,6 .